RETRACTED: Numerical Treatment for 3D Squeezed Flow in a Rotating Channel With Soret and Dufour Effects - Alzahrani, Abdullah K.; Ullah, Malik Zaka; Muhammad, Taseer (Frontiers in Physics, 2020)
This article examines magnetohydrodynamic three-dimensional (3D) squeezed flow by a rotating permeable channel subject to Dufour and Soret impacts. Impact of viscous dissipation is also considered. An applied magnetic field is considered subject to electrically conducting viscous fluid. The change from the nonlinear partial differential framework to the nonlinear ordinary differential framework is assumed into position by utilizing appropriate variables. Governing differential frameworks are computed numerically by shooting method. Numerical results have been achieved by considering numerous values of emerging flow parameters. Contributions of influential parameters on physical quantities are studied thoroughly. Surface drag coefficients and mass and heat transport rates are also processed and examined. Furthermore, the concentration and temperature distributions are reduced for larger values of Soret number. The prime interest of presented study is to model and examine the Dufour and Soret aspects in concentration and energy expressions. To our knowledge, no such analysis has been addressed in the literature yet.